Biological source and provenance of deep-water derived isoprenoid tetraether lipids along the Portuguese continental margin. (1st January 2016) - Kim, Jung-Hyun; Villanueva, Laura; Zell, Claudia; Sinninghe Damsté, Jaap S.
Abstract: There is increasing evidence that nitrifying Thaumarchaeota in the deep ocean waters may contribute to the sedimentary composition of isoprenoid glycerol dialkyl glycerol tetraethers (isoGDGTs), impacting TEX86 paleothermometry. We investigated the potential effect of deep-water dwelling Thaumarchaeota in the warm and saline Mediterranean Outflow Water (MOW) on the distribution of isoGDGTs by analysing suspended particulate matter (SPM) and surface sediments collected along five land-ocean transects along the southern Portuguese continental margin. To this end, we directly compared for the first time the composition of intact polar lipid (IPL)-derived isoGDGTs of SPM with the diversity, abundance, and activity of Thaumarchaeota based on the genetic analysis of the genes coding for the archaeal ammonia monooxygenase ( amo A) and the geranylgeranylglyceryl phosphate (GGGP) synthase involved in the isoGDGT biosynthetic pathway. Our results revealed a strong positive relationship between water depth and TEX 86 H values for both SPM and surface sediments. The increasing TEX 86 H trends for both core lipid (CL) and IPL-derived fractions were accompanied by increasing fractional abundances of GDGT-2 and crenarchaeol regio-isomer and decreasing fractional abundances of GDGT-1 and GDGT-3 with increasing water depth. Phylogenetic analyses based on the archaeal amo A and the GGGP synthase proteins showed that Thaumarchaeota populations detected at 1 m and 50 m water depth were different from those detected in 200 m and 1000 m water depth, which had an increased contribution of so-called 'deep water' Thaumarchaeota. The differences in the fractional abundances of isoGDGTs with water depth were compatible with the increasing contribution of 'deep water' Thaumarchaeota harboring a different GGGP synthase enzyme which has been suggested to relate to changes in the relative proportion of synthesized isoGDGTs. Accordingly, it appears that the sedimentary distribution of CL isoGDGTs used in TEX 86 H along the Portuguese margin is primarily influenced by water depth due to the increasing contribution of the deep-water population of Thaumarchaeota residing in the MOW. Our study also reveals that the effect of deep water Thaumarchaeotal communities on sedimentary isoGDGT distributions should be considered globally.